Long-term analysis of antibodies elicited by SPUTNIK V: A prospective cohort study in Tucumán, Argentina - Rossana Elena Chahla; Rodrigo Hernán Tomas-Grau; Silvia Inés Cazorla; Diego Ploper; Esteban Vera Pingitore; Mónica Aguilar López; Patricia Aznar; María Elena Alcorta; Eva María del Mar Vélez; Agustín Stagnetto; César Luís Ávila; Carolina Maldonado-Galdeano; et al. (Elsevier, 2022)
Summary: Background: Gam-COVID-Vac (SPUTNIK V) has been granted emergency use authorization in 70 nations and has been administered to millions worldwide. However, there are very few peer-reviewed studies describing its effects. Independent reports regarding safety and effectiveness could accelerate the final approval by the WHO. We aimed to study the long-term humoral immune response in naïve and previously infected volunteers who received SPUTNIK V. Methods: Humoral immune responses, assayed by anti-SARS-CoV-2-spike-RBD IgG ELISA and neutralization assays, were measured in 602 healthcare workers at 0, 14, 28, 60 and 180 days after receiving SPUTNIK V between December 2020 and July 2021 in Tucumán, Argentina. Findings: Seroconversion was detected in 97% of individuals after 28 days post-vaccination (dpv) (N = 405). Anti-RBD titers began to decrease after 60 dpv (N = 328), but remained detectable in 94% at 90 dpv (N = 224). At 180 dpv, anti-RDB titers persisted in 31% (N = 146). Previous infection triggered an increased immune response to the first dose and increased neutralization activity against variants of concern (VOC). Second doses in previously infected individuals further increased titers, even 90 dpv (N = 75). Basal antibody titers had more influence on post-vaccination anti-RBD responses than the time elapsed between diagnosis and vaccination (N = 274). Interpretation: Data presented herein provides essential knowledge regarding the kinetics of antibodies induced by SPUTNIK V up to six months after immunization, and suggests that when considering one-dose vaccination policies for individuals with previous SARS-CoV-2 infection, serological studies to determine basal titers may be important, independent of when diagnosis occurred. Funding: Tucumán Public Health System (SIPROSA), Argentinean National Research Council (CONICET), National University of Tucumán (UNT).